MANAJEMEN KURIKULUM MERDEKA DALAM MENINGKATKAN KINERJA GURU SEKOLAH MENENGAH PERTAMA DI KABUPATEN CIANJUR - Sri Retno Kuswahyuni; Ani Kania; Ate Jamaludin Mubarok; Imas Nanan Nuraeni; AD Rima Widianingsih; R. Supyan Sauri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the management of the Merdeka Curriculum in improving teacher performance at junior high schools (Sekolah Menengah Pertama, SMP) in Cianjur Regency, specifically at SMPN 1 Naringgul and SMPN 10 Naringgul. The Merdeka Curriculum is an educational policy that emphasizes student-centered learning, differentiated instruction, and the strengthening of the Pancasila Student Profile. The implementation of this curriculum requires effective management, particularly in the areas of planning, implementation, and evaluation, in order to optimally enhance teacher performance. This research uses a qualitative descriptive method with data collected through in-depth interviews, observations, and documentation. The research informants consist of principals, vice principals in charge of curriculum, and teachers directly involved in implementing the Merdeka Curriculum. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that the management of the Merdeka Curriculum in both schools is conducted systematically and collaboratively. Curriculum planning involves all school stakeholders, learning implementation is adapted to the needs and characteristics of the students, and evaluation is carried out regularly through supervision and teacher reflection. Effective management of the Merdeka Curriculum has proven to contribute positively to the improvement of teacher performance, as demonstrated by increased creativity in teaching, active participation in the development of teaching materials, and commitment to achieving student-centered educational goals. Therefore, a structured and participatory management of the Merdeka Curriculum is a key factor in promoting teacher professionalism and performance at the junior high school level.